Numerical Simulation of Magnetic Field Effect on Cryocooler Regenerators: Temperature Distribution - Rajendra Kumar; Sumit Shoor (Modelling and Simulation in Engineering)
Regenerative types of cryogenic refrigerators (or cryocoolers) employ magnetic intermetallic compounds of 3d and 4f elements to work well below 10 K. This paper presents the analysis of temperature distribution in regenerators of such cryocoolers under the influence of magnetic fields of 1 T, 3 T, and 4.3 T. Commercial code of finite element analysis (FEA) package, ANSYS (APDL) 14.5, is used to investigate the temperature distribution under above-mentioned fields. Er3Ni is selected as regenerator material and the criteria for its selection are discussed in detail. The cold end temperature is varied from 4.2 K to 10 K and hot end temperature is fixed at 20 K. The values obtained from FEA clearly show that the ineffectiveness of Er3Ni is at 8 K and 10 K at 3 T and 4.3 T.